Project Silica: Towards Sustainable Cloud Archival Storage in Glass - Anderson, Patrick; Aranas, Erika B.; Assaf, Youssef; Behrendt, Raphael; Black, Richard; Caballero, Marco; Cameron, Pashmina; Canakci, Burcu; Carvalho, Thales de; Chatzieleftheriou, Andromachi; Clegg, James; Clarke, Rebekah Storan; et al. (The 29th ACM Symposium on Operating Systems Principles, 2023)
Sustainable and cost-effective long-term storage remains an unsolved problem. The most widely used storage technologies today are magnetic (hard disk drives and tape). They use media that degrades over time and has a limited lifetime, which leads to inefficient, wasteful, and costly solutions for long-lived data. This paper presents Silica: the first cloud storage system for archival data underpinned by quartz glass, an extremely resilient media that allows data to be left in situ indefinitely. The hardware and software of Silica have been co-designed and co-optimized from the media up to the service level with sustainability as a primary objective. The design follows a cloud-first, data-driven methodology underpinned by principles derived from analyzing the archival workload of a large public cloud service. Silica can support a wide range of archival storage workloads and ushers in a new era of sustainable, cost-effective storage.